\[\boxed{\mathbf{861\ (861).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[Пусть\ числа\ a_{1},\ a_{2},\ a_{3}.\]
\[Получаем:\]
\[a_{1} + a_{2} + a_{3} = 21\ \]
\[a_{1} + a_{1} + d + a_{1} + 2d = 21\ \ \]
\[3a_{1} + 3d = 21\ \ \ |\ :3,\ \ \]
\[a_{1} + d = 7\ \]
\[\ d = 7 - a_{1}.\]
\[Значит,\ образуют\ \]
\[геометрическую\ \]
\[прогрессию\ числа\ \]
\[a_{1} + 2,a_{2} + 3,a_{3} + 9.\]
\[Отсюда:\]
\[\ \left( a_{2} + 3 \right)^{2} = \left( a_{1} + 2 \right)\left( a_{3} + 9 \right)\]
\[\left( a_{1} + d + 3 \right)^{2} =\]
\[= \left( a_{1} + 2 \right)\left( a_{1} + 2d + 9 \right)\]
\[(7 + 3)^{2} =\]
\[= \left( a_{1} + 2 \right)\left( a_{1} + 2 \cdot \left( 7 - a_{1} \right) + 9 \right),\]
\[10^{2} =\]
\[= \left( a_{1} + 2 \right)\left( a_{1} + 14 - 2a_{1} + 9 \right)\ \]
\[10^{2} = \left( a_{1} + 2 \right)\left( 23 - a_{1} \right),\]
\[100 = 23a_{1} - a_{1}^{2} + 46 - 2a_{1}\text{\ \ }\]
\[a_{1}^{2} - 21a_{1} + 54 = 0\]
\[a_{1} + a_{2} = 21;\ \ a_{1} = 18\]
\[a_{1}a_{2} = 54;\ \ a_{1} = 3\]
\[при\ \ a_{1} = 3 \Longrightarrow \ \ d = 7 - 3 = 4:\]
\[a_{2} = 3 + 4 = 7;\ \]
\[a_{3} = a_{2} + d = 7 + 4 = 11;\]
\[при\ a_{1} = 18 \Longrightarrow d =\]
\[= 7 - 18 = - 11:\]
\[a_{2} = 18 - 11 = 7;\ \]
\[a_{3} = 7 - 11 =\]
\[= - 4 < 0 \Longrightarrow не\]
\[\ удовлетворяет.\]
\[Ответ:3;7;11.\]
\[\boxed{\mathbf{861.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[b_{1} + b_{4} = \frac{35}{3},\ \ b_{2} + b_{3} = 10\]
\[\left\{ \begin{matrix} b_{1} + b_{1}q^{3} = \frac{35}{3} \\ b_{1}q + b_{1}q^{2} = 10 \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ }\]
\[\ \left\{ \begin{matrix} b_{1}\left( 1 + q^{3} \right) = \frac{35}{3}\text{\ \ \ \ \ } \\ b_{1}q(1 + q) = 10\ \ \ \\ \end{matrix} \right.\ \ (\ :)\ \ \]
\[\frac{b_{1}(1 + q)\left( 1 - q + q^{2} \right)}{b_{1}q(1 + q)} = \frac{35}{30}\]
\[\frac{1 - q + q^{2}}{q} = \frac{7}{6}\]
\[7q = 6 - 6q + 6q^{2}\]
\[6q^{2} - 13q + 6 = 0\]
\[D = 169 - 144 = 25\]
\[q = \frac{13 + 5}{12} = 1,5;\ \ \ \ \ \ \ \]
\[\text{\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ }q = \frac{13 - 5}{12} = \frac{2}{3}\]
\[при\ \ q = 1,5:\ \ \]
\[b_{1} = \frac{10}{1,5 \cdot (1 + 1,5)} = \frac{10}{1,5 \cdot 2,5} =\]
\[= \frac{10}{\frac{3}{2} \cdot \frac{5}{2}} = \frac{8}{3} = 2\frac{2}{3};\]
\[b_{2} = \frac{8}{3} \cdot \frac{3}{2} = 4,\ \ \]
\[b_{3} = 4 \cdot \frac{3}{2} = 6,\]
\[\text{\ \ }b_{4} = 6 \cdot \frac{3}{2} = 9.\]
\[при\ q = \frac{2}{3}:1 = 1023 \cdot 1 + \frac{2}{3} =\]
\[= 102 \cdot 53 \cdot 3 = 9,\]
\[\ \ b2 = 9 \cdot 23 = 6,\]
\[b_{3} = 6 \cdot \frac{2}{3} = 4,\ \ \]
\[b_{4} = 4 \cdot \frac{2}{3} = \frac{8}{3}.\]
\[Ответ:\ \ 2\frac{2}{3};4;6;9.\]